How Singing can Help People With Dementia and Their Family Care-Partners: A Mixed Studies Systematic Review With Narrative Synthesis, Thematic Synthesis, and Meta-Integration - Thompson, Zara; Baker, Felicity A.; Tamplin, Jeanette; Clark, Imogen N. (Frontiers in Psychology, 2021)
Background: Recent research on the efficacy of music-based interventions for people with dementia have focused on specific outcomes and methods, and singing has been noted as a particularly beneficial activity. However, due to heterogeneity of research methods, there is a need to synthesise the findings of both quantitative and qualitative research in order to better understand both the impact and potential mechanisms of singing for people in this population. Method: This systematic review included quantitative, qualitative and mixed-methods studies, and analysed these using a systematic mixed-studies synthesis (with a results-based convergent approach). Quantitative and qualitative data were initially synthesised using a narrative synthesis and thematic synthesis method, respectively, before a final meta-integration method was used to synthesise common themes across the two data forms. Results: Electronic and hand search strategies revealed 1,815 relevant studies, 40 of which met the full eligibility criteria. Narrative synthesis of quantitative data revealed six key outcome areas (quality of life; psychological well-being; cognition; engagement; activities of daily living; care-partner well-being), and thematic synthesis of qualitative data generated seven themes relating to the impact and mechanisms of singing (pragmatic elements; social benefits; mood; identity; memory; flow-on effects; and relationships). Meta-integration identified four key areas relating to the impact and mechanisms of singing for people with dementia and care-partners: psychological well-being, quality of life, cognition, and care-partner well-being. Conclusion: Results from the syntheses suggest that singing can positively impact the lives of people with dementia and their care-partners, although due to heterogeneity of study design and outcome measures, it is difficult to draw conclusions based on quantitative data alone. Qualitative data provides further context and insights from participant perspectives, and when integrated with quantitative data, contextual factors that may influence the benefits that participants experience from singing are revealed.